A Thousand Invisible Architects: Vassals, the Petition and Response System, and the Creation of Spanish Imperial Caste Legislation - Masters, Adrian (2022)
This article explains two unique aspects of the New World Spanish empire: its production of hundreds of thousands of royal decrees, and the unique categories that these edicts contained, such as mestizo and mulato. I outline the petition and response system, through which vassals of all social backgrounds constantly suggested new laws to the ruling Council of the Indies. Pressed for time, the council’s overwhelmed ministers often transplanted petitions’ vocabulary verbatim into decrees. This meant that subjects often phrased imperial laws minor and major, regional and Indies-wide. Using a four-step archival methodology, this article demonstrates how scholars can match vassals’ petitions to decrees. This essay then shows how legal categories such as mestizo and mulato came about through the petitions of not only Spaniards but also Indians, mestizos, and mulatos themselves. Subjects of any social background could therefore introduce and shape Indies legal constructs, and the empire’s agenda, from the ground up.